Sosialisasi Penggunaan Aplikasi Mobile Jaminan Kesehatan Nasional (JKN) pada Pasien atau Keluarga BPJS di RS Woodward Palu - Mutmainnah Hasi Hasinuddin; I Gede Restawan; Sri Purwiningsih; Anggri Alfira Yunita Assa; Imelda Kantohe; Prince Credo N. Togea; Riski Kurniawan Dawali; Muthmainnah Munir (Universitas Baiturrahim, 2026)
This era of reform has caused the development of information technology to grow rapidly,BPJS has a brilliant idea by lauching the JKN Mobile Application,the application is an innovation carried out by BPJS Kesehatan in Improving services to the community in the health sector .Mobile phones are a tool to help communicate and solve problems in health services,accelerate access,this application needs to be known and disseminated ,the use ofe the JKN mobile application has minimal information,but there are also people who understand but fail to register .Even through the application can facilitate patients in JKN health administration activities,Community Service Community Service is carried out at the Woodward Palu Hospital which is a PkM partner location aimed at ensuring that Patients/families can inderstand and the able to apply the use of the JKN Mobile application effectively,we and the officers direct and guide the use of registrasion through the machine provided at the hospital and are directed back to the JKN Mobile Application and filling out the questionnaire using a barcode scan.This activity was carried out for days,there were 40 BPJS user patiens using the JKN Mobile Application.